Intertextuality - Allen, Graham (London Routledge, 2000)
This book follows all the major turns in intertextuality's history, and explains how intertextuality is employed. It is invaluable for any student studying literature and culture.
Keywords: Intertextuality. TRAVEL -- Special Interest -- Literary. LITERARY CRITICISM -- General